United Kingdom : Financial Sector Assessment Program Technical Notes and Detailed Standards Assessments. (IMF Staff Country Reports; Country Report, 2003)
This technical note reviews the Financial Sector Assessment Program of the United Kingdom. It examines the United Kingdom's public debt management practices using the IMF-World Bank Guidelines for Public Debt Management as a framework. It analyzes the government's Code for Fiscal Stability, transparency, accountability, debt strategy, and risk management framework. It also provides a detailed assessment of the antimoney laundering and combating the financing of terrorism regime and compliance of the Basel Core Principles of the United Kingdom.